Safety and efficacy of pharmacological approaches available for multisystem inflammatory syndrome in children (MIS-C): a systematic review - Velusamy, Yasothaa; Yubbu, Putri; Romli, Muhammad Hibatullah; Aissvarya, Shankar; Thilakavathy, Karuppiah; Vivekanandan, Govinathan (International Children's Center (ICC), Uluslararasi Cocuk Sagligi Merkezi, 2022)
Background. To describe the existing pharmacological managements for Multisystem Inflammatory Syndrome in Children (MIS-C) in a systematic way, to identify the available pharmacological managements in MIS-C, evaluate its safety and efficacy and identify the best treatment procedures for practice recommendation.Methods. A systematic search using six databases was conducted on August 18, 2021, updated in January 26th 2023. Terminologies that were used in this search are children, MIS-C/PIMS and SARS-CoV-2. A PRISMA flow diagram was used to report the study selection process. Quality analysis was done based on NOS and GRADE tools. Data synthesis was conducted by extracting the information on drugs used, efficacy and side effects.Results. From the 32 articles included, a total of 2331 children with MIS-C were studied. The main pharmacological approaches were immunomodulatory therapy, i.e., intravenous immunoglobulin (IVIG) (77.3%), steroids (60.5%), and a combination of IVIG and steroids (41.3%). IVIG and steroids were found to be potentially effective and safe treatments for MIS-C. Combination of IVIG and steroids was found favorable in severe cases with higher recovery rate. Refractory treatments include second dose of initial treatment and biological response modifier drugs like anakinra, tocilizumab, infliximab. A small number of studies investigating supportive treatment consisted of vasoactive, inotropic and anticoagulation. The mortality rate was 1.28% and only three studies reported side effects from the treatment. Evidence of outcome from GRADE were mostly at moderate, low and very low levels.Conclusions. This review provides preliminary evidence to support the current standard treatment practices in managing MIS-C pharmacologically. However, comprehensive investigation is required using clinical trials to provide stronger outcome evidence.